1999
DOI: 10.1051/rnd:19990507
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of intestinal digestibility of undegraded sunflower meal protein from nylon bag measurements. A mathematical model

Abstract: -Ruminal nitrogen degradation and intestinal digestibility (ID) of the undegraded nitrogen of three sunflower meals were determined on three wethers fitted with rumen cannulae and T-type duodenal cannulae using nylon bags. Meals were obtained from semi-dehulled seeds by conventional hexane extraction (samples SD1 and SD2) or from whole seeds by a discontinuous procedure of pressing and hexane extraction (sample W), which causes a superior thermal effect. Therefore, effective degradability of nitrogen for the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 12 publications
5
42
0
6
Order By: Relevance
“…Thus, the lower values of IED of CP recorded for orthophosphoric acid than for malic acid may be associated with its higher impact on the increase in the r fraction and therefore of indigestible nitrogenous compounds in the intestine. Gonzá lez et al (1999) also showed increases in IED of CP, with the increase in the CP BP when comparing SFMs resulting from different industrial processes. The large increased supply of intestinal digested CP from treated meals can also be associated with a decrease in the microbial protein synthesis in the rumen derived from these meals because of their reduced fermentation.…”
Section: Ruminal Fermentation and Digesta Kineticsmentioning
confidence: 82%
“…Thus, the lower values of IED of CP recorded for orthophosphoric acid than for malic acid may be associated with its higher impact on the increase in the r fraction and therefore of indigestible nitrogenous compounds in the intestine. Gonzá lez et al (1999) also showed increases in IED of CP, with the increase in the CP BP when comparing SFMs resulting from different industrial processes. The large increased supply of intestinal digested CP from treated meals can also be associated with a decrease in the microbial protein synthesis in the rumen derived from these meals because of their reduced fermentation.…”
Section: Ruminal Fermentation and Digesta Kineticsmentioning
confidence: 82%
“…However, in our work, dehydration only led to a moderate reduction of ED (6.1%). No other effects of this reduction should be expected on the feed nitrogen value since different studies carried out with different feeds [10,13] indicate that heat treatments yielding no heat damage, improve the content of by-pass protein without impairing intestinal digestibility of this fraction, in spite of the increased nitrogen fibrebound contents of the feeds.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal disappearance (ID) of undegraded material (DM or CP) was calculated as the amount lost from the bag divided by the amount in the bag before the intestinal passage. Then, the evolutions of the ID values with the rumen pre-incubation time were fitted for each animal to different functions in relation to feed to determine IED by the method proposed by González et al [1]. To obtain the effective proportion digested in the intestine of a feed fraction, these authors propose to consider together the functions which describe (1) the variation of its ID with the rumen incubation time, and (2) the outflow of undegraded material from the rumen.…”
Section: Intestinal Digestibilitymentioning
confidence: 99%
“…On the contrary, the mobile nylon bag technique, based on the incubation of rumen pre-incubated feed samples in bags that transit between the duodenum and the ileum or the anus, is a simple and adaptable method that can be used in systematic studies. The main limitation of this method is derived from the variation of the ID values with the rumen pre-incubation time in many types of feeds [1,2], as a consequence of the changes in the concentrations of undigestible nitrogenous compounds in the small intestine caused by the rumen microbial actions. This limitation can be avoided by the estimation of the intestinal effective digestibility (IED) of the feed protein from measurements with mobile bags weighed according to the rumen outflow of undegraded protein [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation